2020
DOI: 10.21837/pm.v18i11.712
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood Quality Assessment: A View of Tenure Ownership and Mobility Decisions in Penang, Malaysia

Abstract: Most people have experienced a crucial moment of decision during their life course, that of whether to stay over or to move out of their house and neighbourhood. Residential mobility refers to mobility thoughts and intentions, as well as the actual moving behaviours among the residents, which are often triggered by feelings of dissatisfactions, state of disequilibrium or mismatch between the present housing needs and consumption, and the desired housing preferences. Residential mobility is postulated to be inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The study (Abdul Fattah et al, 2020) found that home features, neighbourhood facilities, environment, social contact, and attachment are the primary concerns and preferences influencing residential mobility behaviours among people.…”
Section: Housing Preferencesmentioning
confidence: 95%
“…The study (Abdul Fattah et al, 2020) found that home features, neighbourhood facilities, environment, social contact, and attachment are the primary concerns and preferences influencing residential mobility behaviours among people.…”
Section: Housing Preferencesmentioning
confidence: 95%
“…The people-place relationship is emphasising on the human values practised in the livelihood as a society rather than specific subjects such as river and community resilience. For example, the interaction with neighbours radiating positive vibes enhance their sense of attachment towards their everyday living landscape (Fattah, Badarulzaman, & Ali, 2020). In the matter of river and community resilience, the element of attachment was discovered essential for the community to be able to appreciate the living environment.…”
Section: Tabel 1 Summary Of Articles Found In River Community Resilmentioning
confidence: 99%
“…Despite these issues, the people continued to reside in the neighbourhood. A study by Fattah et al (2020) found that the residents of a neighbourhood stay because of tenure ownership and perception of neighbourhood quality. However, the riverside community's residence is related to the community's ability to cope with disturbances.…”
Section: River Issuesmentioning
confidence: 99%